Electron interference in fast ion collisions with H2 and the frequency parameter - Chatterjee, S. (2011)
The Young-type interference effect has been investigated in electron emission from molecular hydrogen in collision of 5MeVu−1 F9+ ions. The double differential cross section ratios of molecular-to-atomic hydrogen exhibits oscillatory structure, which is discussed in terms of the Young-type electron interference. We have obtained the frequencies of such oscillation for different angles. A comparative study of the frequency parameter is given with early measurements performed by other groups.